Graphene Oxide Mediated Broad-Spectrum Antibacterial Based on Bimodal Action of Photodynamic and Photothermal Effects - Romero, María Paulina; Marangoni, Valeria Spolon; de Faria, Clara Gonçalves; Leite, Ilaiali Souza; Silva, Cecília de Carvalho Castro e; Maroneze, Camila Marchetti; Pereira-da-Silva, Marcelo A.; Bagnato, Vanderlei Salvador; Inada, Natalia Mayumi (Frontiers in Microbiology, 2020)
Graphene Oxide (GO) with their interesting properties including thermal and electrical conductivity and antibacterial characteristics have many promising applications in medicine. The prevalence of resistant bacteria is considered a public health problem worldwide, herein, GO has been used as a broad spectrum selective antibacterial agent based on the PTT / PDT effect. The preparation, characterization, determination of photophysical properties of two different sizes of graphene oxide is described. In vitro light dose and concentration-dependent studies were performed using Gram-negative E. coli and Gram-positive S. aureus bacteria based on the PTT / PDT effect used ultra-low doses (65mW cm-2) of 630 nm light, to achieve efficient bacterial decontamination. The results show that GO and nGO can sensitize the formation of 1O2 and allow a temperature rise of 55° C to 60 ° C together nGO and GO to exert combined PTT/PDT effect in the disinfection of gram-positive S. Aureus and gram-negative E. Coli bacteria. A complete elimination of S. Aureus and E. Coli bacteria based on GO and nGO is obtained by using a dose of 43-47 J cm-2 for high concentration used in this study, and a dose of around 70 J cm-2 for low dose of GO and nGO. The presence of high concentrations of GO allows the bacterial population of S. aureus and E. coli to be more sensitive to the use of PDT/PTT and the efficiency of S. aureus and E. coli bacteria disinfection in the presence of GO is similar to that of nGO. In human neonatal dermal fibroblast, HDFs, no significant alteration to cell viability was promoted by GO, but in nGO is observed a mild damage in the HDFs cells independent of nGO concentration and light exposure. The unique properties of GO and NGO may be useful for the clinical treatment of disinfection of broad-spectrum antimicrobials. The antibacterial results of PTT and PDT using GO in gram-positive and gram-negative bacteria, using low dose light, allow us to conclude that GO and nGO can be used in dermatologic infections, since the effect on epithelial cells of this treatment is low compared to the antibacterial effect.